A Study Analysis of The Comparative Effectiveness of Transurethral Prostate Resection And Holmium Laser Enucleation In Benign Prostatic Hyperplasia - Budi, Agus; Farida (International Medical Journal Corp. Ltd, 2024)
Background: Benign prostatic hyperplasia (BPH) is a prostate condition causing bladder obstruction, kidney damage, and obstructive nephropathy. Treatment options include medication, surgery, and lifestyle changes. Holmium laser enucleation (HoLEP) is a desirable substitute. Methods: Holmium and BPH are related terms in the study of holmium laser enucleation, with the search conducted using MeSH terms. The results were screened by two reviewers, with a third reviewer consulted if consensus was not reached. The study aimed to understand the relationship between holmium and BPH, focusing on the use of holmium in prostate cancer treatment. Result: BPH patients undergoing HoLEP and TURP prostate treatment showed similar outcomes, including shorter hospital stay, reduced operative time, and improved postoperative IPSS, but no significant difference was observed. Conclusion: HoLEP is a surgical technique that has demonstrated potential benefits over Transurethral Resection of the Prostate (TURP). It may be better for incidental prostate cancer detection due to better hemostatic control and fewer side effects, and it may also shorten hospital stays and operating times. Additionally, it may improve the International Prostate Symptom Score and postoperative post-residual volume.